Effect of monospecific bacterial biofilm on mean settlement of the sessile marine invertebrates: Pocillopora damicornis and Amphibalanus amphitrite - Neo, He Xiang (2018)
The increasing trend of natural coastline alternation in coastal cities like Singapore calls for a deeper understanding of its impact on biodiversity on seawalls. This study aimed to evaluate the effectiveness of biofilms on the settlement of two widely studied marine invertebrates, Pocillopora damicornis and Amphibalanus amphitrite. A series of treatments was formulated, based on different monospecific Thalassotalea spp. and Vibrio cholerae biofilms, substrata used and biofilm age. A droplet settlement assay (n = 5) was conducted on competent P. damicornis larvae and A. amphitrite cyprids. The mean settlement, pelagic and mortality of these marine invertebrates were recorded after 24 h. Study results were analysed by PERMANOVA and subsequent post-hoc analysis pairwise tests were performed to test for significant differences between treatments. The different monospecific biofilms and substrata tested revealed differing inductive capabilities and preference respectively on both marine invertebrates. Biofilm age did not show a significant difference on settlement of the two organisms. An increase in biomass of biofilm established has seen an increase in inductive capability observed. The data provided here have broadened our understanding of incorporating biofilms to improve the ecological capacity of an engineered seawall, to serve as an adequate replacement of the natural coastline.